THE INFLUENCE OF HARVESTED AREA, SUGARCANE PRODUCTION, AND INTEREST RATES ON ECONOMIC GROWTH IN INDONESIA - Samuel Sihombing; Cut Putri Mellita Sari; Saharuddin; Syarifah Syafira; Asnawi (LPPM Universitas Malikussaleh, 2026)
This study aims to analyze the effect of sugarcane harvested area, sugarcane production, and interest rates on economic growth in Indonesia. The data used in this study are time series data covering a period of 35 years, from 1990 to 2024. The data were obtained from the Ministry of Agriculture and the World Bank and were analyzed using the Vector Error Correction Model (VECM) approach. The results of this study indicate that, in the short run, the harvested area of sugarcane has a positive and significant effect on economic growth in Indonesia, while interest rates have a positive but insignificant effect. Meanwhile, sugarcane production has a negative and significant effect on economic growth in Indonesia. In the long run, the harvested area of sugarcane and interest rates have a positive and significant effect on economic growth in Indonesia, whereas sugarcane production has a negative and significant effect on economic growth in Indonesia.